Analysis of Students' Problem-Solving Skills in Newton's Law with 5E Learning Cycle - Desyana, Nidya; Sutopo, Sutopo; Mufti, Nandang (Jurnal Pendidikan Sains, 2024)
The aim of this study is to identify students’ problem-solving skills in Newton’s laws through the implementation of the 5E learning cycle in the classroom. A pre-experimental design with a one-group pretest-posttest approach was employed. Data on problem-solving skills were collected from students’ pre-test and post-test responses to two essay questions. The indicator with the highest percentage of problem-solving skills was useful description (83% of students), while the indicator with the lowest percentage was specific application of physics (33% of students). Due to the non-normal distribution of the data, the Wilcoxon test was utilized. The results indicated a significant difference in students’ problem-solving abilities between the pretest and posttest, with a significance value less than 0.05. Consequently, normalized-gain scores were used to further evaluate the improvement in students’ problem-solving skills following the 5E learning cycle. The findings reveal an increase in problem-solving skills, with an N-Gain of 0.63, categorized as medium. This suggests that the 5E learning cycle effectively enhances students’ problem-solving abilities.DOI: 10.17977/jps.v12i42024p152